Perception of customer satisfaction on Al-Rahn Yapiem servicing in Kuantan, Pahang / Nur Asilah Abu Bakar - Abu Bakar, Nur Asilah (Academy of Contemporary Islamic Studies, 2018)
The purpose of this study was to examine the extent to which perceptions of customer satisfaction with the quality of service offered by the Ar-Rahn Yapiem Kuantan based on demographic and dimensions of service quality. Respondents for this survey were Ar-Rahn Yapiem Kuantan customers, and a total of 100 questionnaires were distributed by using convenience sampling technique. The design of this study is a case study survey using a quantitative approach. Questionnaires were used as an instruments for obtaining data. The data were analyzed using the Statistical Package for Social Science (SPSS) program version 20. Analysis used in this study is a frequency and descriptive analysis. Results of the study showed that 51.9% of women customers are more satisfied using the ArRahn services rather than male customer. Empathy factor is a critical factor while the other question is less tangible factors. In conclusion, the customers are satisfied with the quality of service provided by Ar-Rahn Kuantan.